Natura Naturata (An Argument for Still Life) : Benefit Exhibition for Squat Theatre / Joseph Kosuth. - Carrà, Carlo; Clegg & Guttmann; DaRosa, Raquel; Dimitrijevic, Braco; Fanshaw, Daniel; Lauf, Cornelia; Magriel, Paul; Welchman, John, C. (New York : Josh Baer Gallery, 1989)
Belcher, Alan ; Büttner, Werner ; Charlesworth, Sarah ; Clegg & Guttmann ; Dimitrijevic, Braco ; Dujourie, Lili ; Kosuth, Joseph ; Lichtenstein, Roy ; Manet, Edouard ; O'Brien, Glenn ; Oldenburg, Claes ; Pistoletto, Michelangelo ; Schaerf, Eran ; Staehle, Wolfgang ; Steinbach, Haim ; Tower, Jon
Checklist & Bibliography [25 p.]
Engels
Natura Naturata (An Argument for Still Life), Josh Baer Gallery, New York, March 4-11, 1989
kunstcatalogus